Dissecting Aneurysms of the Distal Segment of the Posterior Inferior Cerebellar Arteries: Clinical Presentation and Management - Lim, S.M.; Choi, I.S.; Hum, B.A.; David, C.A. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Dissecting aneurysms of the distal segment of the PICA are rare. The purpose of this study was to evaluate the clinical presentations, imaging features, treatment options, and clinical outcomes of dissecting PICA aneurysms. MATERIALS AND METHODS: Six patients with dissecting aneurysms in the distal segments of PICA were found in the database of a single medical center, from November 1996 to December 2008, and retrospectively evaluated. Treatment mode and follow-up clinical outcomes were analyzed. RESULTS: Five patients with dissecting PICA aneurysms presented with acute intracranial hemorrhage and 1 patient presented with a large mass from an intramural hematoma. All 5 patients with intracranial hemorrhage were treated with endovascular occlusion of both the dissecting PICA aneurysm and the distal parent artery. The patient with the intramural hematoma underwent surgical trapping with end-to-end anastomosis. In 1 patient, the dissecting aneurysm recurred twice within a 5 year 3 month period, despite endovascular occlusion of both the aneurysm and the parent artery. The clinical outcome postprocedure was excellent in all patients, without permanent neurologic complication. CONCLUSIONS: For the endovascular treatment of dissecting aneurysms in the distal PICA segments, we recommend occlusion of both the dissecting aneurysm and the parent artery to avoid leaving the point of initial intimal tear untreated. All of our patients had excellent clinical outcomes; however, our experience with recanalization illustrates the need for close follow-up of patients. PICAposterior inferior cerebellar arterySAHsubarachnoid hemorrhage